Spatiotemporal Alterations in Gait in Humanized Transgenic Sickle Mice - Kiven, Stacy; Wang, Ying; Aich, Anupam; Argueta, Donovan A.; Lei, Jianxun; Sagi, Varun; Tennakoon, Madhushan; Bedros, Saad J.; Lambrecht, Nils; Gupta, Kalpna (Frontiers in Immunology, 2020)
Sickle cell disease (SCD) is a hemoglobinopathy affecting multiple organs and featuring acute and chronic pain. Purkinje cell damage and hyperalgesia have been demonstrated in transgenic sickle mice. Purkinje cells are associated with movement and neural function which may influence pain. We hypothesized that Purkinje cell damage and/or chronic pain burden provoke compensatory gait changes in sickle mice. We found that Purkinje cells undergo increased apoptosis as shown by caspase-3 activation. Using an automated gait measurement system, MouseWalker, we characterized spatiotemporal gait characteristics of humanized transgenic BERK sickle mice in comparison to control mice. Sickle mice showed alteration in stance instability and dynamic gait parameters (walking speed, stance duration, swing duration and specific swing indices). Differences in stance instability may reflect motor dysfunction due to damaged Purkinje cells. Alterations in diagonal and all stance indices indicative of hesitation during walking may originate from motor dysfunction and/or arise from fear and/or anticipation of movement-evoked pain. We also demonstrate that stance duration, diagonal swing indices and all stance indices correlate with both mechanical and deep tissue hyperalgesia, while stance instability correlates with only deep tissue hyperalgesia. Therefore, objective analysis of gait in SCD may provide insights into neurological impairment and pain states.